Självstyre eller samförvaltning? : problem och möjligheter utifrån en studie av världsarvet Laponia - Rådelius, Christina (Luleå, 2002)
Because of its importance for indigenous biodiversity and the local Sami culture, the Laponian area, in the north of Sweden, was declared a World Heritage Site Area by the UN organization UNESCO in 1996. Most of the area is protected because it encompasses national parks and nature reserves and is state owned, and, thus, managed by the County Administrative Board. Local stakeholders who want to participate and influence both the policy-making process as well as management activities have recently questioned this top- down arrangement. The issue is complex with stakeholders on different levels, overlapping jurisdictions and pending questions of indigenous rights. In this thesis, different problems are identified that have to be solved in order to promote and maintain a sustainable development of Laponia. The thesis aims to analyze if the adoption of multi-stakeholder co- management of Laponia is a possible solution to above-mentioned problems. A key question is how to understand the concept of co-management in this specific issue. Yet another question is, if and how, decision-making can be delegated to a local management organization. With the basis in common-pool resource theory, it is discussed whether or not, self-organization and self- governance of the area is a probable solution. It is concluded that one way of dealing with this problematic issue could be to create a co-management system for the Laponian area. I december 1996 utsåg FN-organet Unesco Laponiaområdet i Norrbottens län till världsarv på grund av dess unika natur- och kulturvärden. Världsarvet Laponia är 9.400 km² stort och uppbyggt kring fyra nationalparker och två naturreservat. Det är också det empiriska fall som behandlas i denna uppsats. Den svenska naturvården har under lång tid varit formad med ett ovanifrånperspektiv, det vill säga den har varit hierarkiskt och statligt styrd. Under senare år har dock i flera delar av landet, allt tydligare krav ställts från lokal nivå, om delaktighet i förvaltningen av naturresurserna. Laponia är ett ...